JAVA DISTRIBUTED COMPONENTS FOR NUMERICAL VISUALIZATION IN VISAD. - Hibbard, William; Rueden, Curtis; Emmerson, Steve; Rink, Tom; Glowacki, David; Whittaker, Tom; Murray, Don; Fulker, David; Anderson, John (Communications of the ACM, 2005)
The article focuses on Visualization for Algorithm Development, or VisAD, library of Java components to overcome the limitations imposed on numerical visualization. For new users, the VisAD library is a challenge due to its high level of abstraction. Their first step is usually to visualize their data in the VisAD SpreadSheet, which provides access to much of the library via a GUI. The user-interface component in Figure 1 is part of that GUI, helping users learn about the data schema grammar and the display mappings. The VisAD library is being used to write traditional visualization applications that assume specific data structures and depictions. These applications typically require a few hundred to a few thousand lines of Java. The library distribution includes approximately 12 such applications as examples for new users. The VisAD library is being used to support applications that do not assume specific data structures and depictions. They are continuing projects requiring years of development.